KORELASI ANTARA EFEKTIFITAS KEGIATAN AMAL BAKTI SANTRI (ABAS) DENGAN EMPATI SISWA KELAS VIII PUTERI SMP MUHAMMADIYAH BOARDING SCHOOL YOGYAKARTA BOARDING SCHOOL - Risma Nur Amalina (Jurnal Pendidikan Agama Islam, 2017)
Studens have to have emphaty about their friends condition, but the truth is the middle to high class family students have less emphaty to their friends condition who come from low class family. Therefore, conducted research on the correlation between the effectiveness of amal bakti santri(ABAS) program with student’s emphaty. This research is a field research that take 78 studens as random sample. The data is collected using questionnaire, interview dan observation method. The results showed that : 1) the level of emphaty class VIII students in Muhamadiyah Boarding School Yogyakarta classified in the high category with an average value of 86,69. 2) effectiveness of the amal bakti santri (ABAS) with the average value of 85,7. 3) There was a significant positive correlation between the effectiveness of amal bakti santri (ABAS) program with student’s emphaty class VIII in Muhamadiyah Boarding School Yogyakarta with r count (0,338) >r table (0,227). This means that the effective amal bakti santri (ABAS) program will increase the student’s emphaty.